1983
DOI: 10.2307/1367889
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Rate of Tropical Birds

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press and CooperOrnithological Society are collaborating with JSTOR to digitize, preserve and extend access to The Condor.ABSTRACT. -Oxygen consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 11 publications
3
50
1
Order By: Relevance
“…The majority (28 out of 49 measurements) differed by more than 20% from the predicted values; the extremes being 69% of the predicted value in the Magnificent Frigatebird Fregata magnijicens (1078 g) and 200% in the Glaucous Gull Larus hyperboreus (1200 g). Much of this variation around predicted levels can be related to geographic distribution, as was already shown for terrestrial birds by Weathers (1979) and Hails (1983). Among 16 species of Charadriiformes (mainly Laridae) the ratio between measured and predicted BMR increased from 0.8 in the tropics to 1.8 in arctic breeding species (Ellis 1984).…”
Section: Speciesmentioning
confidence: 55%
“…The majority (28 out of 49 measurements) differed by more than 20% from the predicted values; the extremes being 69% of the predicted value in the Magnificent Frigatebird Fregata magnijicens (1078 g) and 200% in the Glaucous Gull Larus hyperboreus (1200 g). Much of this variation around predicted levels can be related to geographic distribution, as was already shown for terrestrial birds by Weathers (1979) and Hails (1983). Among 16 species of Charadriiformes (mainly Laridae) the ratio between measured and predicted BMR increased from 0.8 in the tropics to 1.8 in arctic breeding species (Ellis 1984).…”
Section: Speciesmentioning
confidence: 55%
“…Indeed several studies, particularly in birds, have suggested that metabolic rates increase with latitude (Kendeigh 1944;Kendeigh & Blem 1974;Ricklefs 1976;Vleck & Vleck 1979;Weathers 1979;Bryant & Hails 1983;Hails 1983;Klaassen et al 1989;Klaassen & Drent 1991;Klaassen 1995;Weathers 1997). However, latitude was not the only factor affecting metabolic rate in these studies.…”
Section: Introductionmentioning
confidence: 75%
“…BMR is a highly flexible phenotypic trait (Piersma, 2002) and varies both with season (Aschoff and Pohl, 1970;Cooper and Swanson, 1994;Piersma et al, 1995;Liknes and Swanson, 1996;Kvist and Lindström, 2001;Cooper, 2002;Liknes et al, 2002) and geographic location (Weathers, 1979;Kersten et al, 1998;Kvist and Lindström, 2001;Broggi et al, 2004). Several studies showed higher levels of BMR at high latitudes, either within migratory species alternating between tropical and arctic climates, or interspecifically when comparing sedentary species (Weathers, 1979;Hails, 1983;Kersten et al, 1998, Kvist andLindström, 2001;Tieleman and Williams, 2002;Tieleman et al, 2003;Broggi et al, 2004). It is not clear, however, whether an increase in BMR would actually contribute to improved cold tolerance or simply reflect the physiological upregulation necessary to tolerate prolonged periods of cold.…”
Section: Introductionmentioning
confidence: 99%